North American Glaciations and Pacific Inputs in the Nd and Sr Isotope Pleistocene Record From the Western Arctic Ocean. Issue 10 (17th October 2022) - Muratli, Jesse M.; Polyak, Leonid; Haley, Brian A.; Kuznetsov, Anton
Abstract: Enduring questions remain regarding the transition from relatively warm and stable pre‐ and early‐Pleistocene climate to that of the high amplitude glacial‐interglacial cycles later in the Quaternary. The main shift in glacial intensity and periodicity around 1 Ma is known as the Mid‐Pleistocene Transition (MPT). Here we analyze detrital strontium (Sr) and neodymium (Nd) isotopes in a western Arctic sediment core P23 previously investigated using several litho/biostratigraphic proxies. Based on an improved age framework combining lithostratigraphic cyclicity and Sr isotope stratigraphy, the P23 record extends to ∼3.3 Ma, thus providing a rare insight into the Quaternary Arctic climate change. The distinct pre‐MPT P23 record is dominated by Pacific‐sourced sediment inputs, with little to no intra‐Arctic glacial inputs, except for a sandy interval around ∼2.5 Ma. A consistent decrease of Nd isotopic values toward North American continental signatures started in both the Arctic and Bering Sea at ∼1.5 Ma and led to a major threshold shift in P23 proxies at ∼0.9 Ma. We argue that this threshold was associated with the first prolonged closure of the Bering Strait for an entire obliquity cycle. This shift marked the expansion of the North American ice sheets to the Arctic margin, with dramatic impacts on depositional and hydrographic environments in the Arctic Ocean. These impacts intensified in the subsequent glacial intervals indicating further ice‐sheet growth, probably fed back by continuing prolonged Bering Strait closures. Plain Language Summary: A significant change in Earth's climate system, the Mid‐Pleistocene Transition (MPT), happened around 1 million years ago and caused ice‐ages to become longer and colder. To improve our understanding of this transition we analyzed the isotopes of strontium (Sr) and neodymium (Nd) in a marine sediment core from the Western Arctic Ocean. Based on this and previous work done on the same core, we show that material mostly came from the south through the Bering Strait in the first half of our record. The isotopic ratios of Sr and Nd in our core indicate an increasing contribution of material from the North American continent starting around 1.5 million years ago, building up to the MPT when larger sediment grains abruptly appear; an indication of massive ice sheet growth and a resulting discharge of icebergs into the Arctic Ocean. We argue that this major change happened coincident with the first time the Bering Strait was closed—due to a sea level drop caused by the growth of ice on land—through an interglacial period. After this event, subsequent massive ice sheets and prolonged Bering Strait closures worked together to create longer and colder glacial periods than were seen before the MPT. Key Points: We measured strontium and neodymium isotope ratios on the lithogenic fractions of a sediment core from the Western Arctic The sediment record covers the past 3.3 million years of change in the Arctic, a critical and understudied time period in this region Prolonged closures of the Bering Strait are important to the intensification of glacial cycles at the Mid‐Pleistocene Transition